THE EFFECTIVENESS COMPARISON BETWEEN THE METACOGNITIVE APPROACH BASED ON CONTEXTUAL PROBLEMS AND THE SCIENTIFIC APPROACH IN TERMS OF MATHEMATICAL REASONING ABILITY OF THE SENIOR HIGH SCHOOL STUDENTS IN THE LEARNING OF MATHEMATICS - Lisa Febrianti; Ali Mahmudi (Jurnal Pedagogi Matematika, 2016)
This study aimed to determine: (1) the effectiveness of scientific approach in terms of mathematical reasoning ability of the senior high school students in the learning of mathematics, (2) the effectiveness of the metacognitive approach based on contextual problems in terms of mathematical reasoning ability of the senior high school students in the learning of mathematics, and (3) the effectiveness comparison of the metacognitive approach based on contextual problems and the scientific approach in terms of mathematical reasoning ability of the senior high school students in the learning of mathematics. This research is quasi-experiment with the pretest and posttest design with nonequivalent comparison-control group. The population in this research was all of the students of X MIA of SMA Negeri 1 Purworejo which consisted of 8 classes. The samples were selected using the random cluster sampling technique with class of X MIA 2 as the experimental class which implemented the mathematical learning with the metacognitive approach based on contextual problems and class of X MIA 1 as the control class which implemented the mathematical learning with the scientific approach. The learning at each class was supported by worksheets given by the teacher. The instruments in this reasearch were learning observation sheets and mathematical reasoning ability tests consisting of pretest and posttest. The effectiveness test of the learning used one sample t-test, while the effectiveness comparison test used independent sample t-test assisted by the SPSS version 23 for windows with a significance level of 5%. The result of this research showed that (1) the scientific approach is effective in terms of mathematical reasoning ability of the senior high school students in the learning of mathematics, (2) the metacognitive approach is effective in terms of mathematical reasoning ability of the senior high school students in the learning of mathematics, and (3) the metacognitive approach based on contextual problems is more effective than the scientific approach in terms of mathematical reasoning ability of the senior high school students in the learning of mathematics.  Keywords:  metacognitive approach, contextual problems, scientific approach, mathematical reasoning ability